Do Children Need Adult Support During Sociodramatic Play to Develop Executive Functions? Experimental Evidence - Veresov, Nikolai; Veraksa, Aleksander; Gavrilova, Margarita; Sukhikh, Vera (Frontiers in Psychology, 2021)
The cultural-historical approach provides the deep theoretical grounds for the analysis of children's play. Vygotsky suggested three critical features of play: switching to an imaginary situation, taking on a play role, and acting according to a set of rules defined by the role. Collaboration, finding ideas and materials for creating an imaginary situation, defining play roles, and planning the plot are complex tasks for children. However, the question is, do children need educator’s support during the play to develop their executive functions, and to what extent? This experimental study was aimed at answering this inquiry. The four modes of sociodramatic play were created which differed in the adult intervention, from non-involvement in the play to its entire organization. The play could be child-led (with adult help), adult-led, or free (without any adult intervention); and there was also a control group where the children heard the same stimulus stories as the other groups but then followed them up with a drawing activity instead of a play activity. The study revealed that, firstly, the ways of educator’s involvement in the play differed in their potential in respect to the development of executive functions, and, secondly, this influence was not equal for different components of executive functions. Free play in the experiment was not a beneficial condition for the development of any of the studied components of executive functions, compared to the conditions involving the participation of an adult in the play. Furthermore, the type of adult intervention stimulated the development of various executive functions. The entire organization of the play by the adult had a positive impact of their general development. In contrast, the adult's assistance in the organization of the children’s play had a positive effect on the development of inhibitory control. The study results can be helpful when considering educational practices within a cultural-historical approach to engaging the potential of play in children’s learning and development around the world.